Evaluation of Factors in the Incident of Hypertension in the Elderly and Analysis and Prevention Strategies - Agustina, Dewi; Syafira, Azzahra Chandra; Febrina, Dea; Diwanta, Faradilla; Siregar, Jelita Suryani; Farashati, Junaisa Intan; Marwa , Nabilah Aprilia; Ramadiah, Putri Suci; Megarani, Sheila; Gunawan, Muhammad Khair; Purba, Elsa Yoreina; Ningtias, Afri (Universitas Ibn Khaldun Bogor, 2024)
High blood pressure, also called hypertension, is a medical condition where blood pressure increases above normal, namely 140/90 mmHg, and carries a risk of illness or death (mortality). This disease is often called a silent disease. Irreversible hypertension and modifiable hypertension are two categories of hypertension risk factors. Smoking, obesity, stress, and a monotonous lifestyle are modifiable factors that can cause hypertension. In this research, secondary data is used. The data used comes from previous research, not from going directly into the field. The research sample received in previous research was 52 people. This research was conducted in Namorih Village, Pancur Batu District, Deli Serdang Regency, North Sumatra, with the aim of revealing how lifestyle and diet have an impact on the number of hypertension cases. The research results show that there are things that can be done to control hypertension, such as changing lifestyles and habits. Genetic factors, daily lifestyle, and daily habits, including smoking, excessive salt consumption, lack of physical activity, poor sleep quality, stress, and alcohol consumption, are causes of hypertension in the elderly. Many people around the world are affected by hypertension, which is a complex health problem. To prevent complications, people should regularly control their blood pressure and live a healthy lifestyle by exercising and reducing their consumption of fatty foods.